2019
DOI: 10.1029/2018jc014786
|View full text |Cite
|
Sign up to set email alerts
|

Air‐Sea Gas Transfer: Determining Bubble Fluxes With In Situ N2 Observations

Abstract: Oxygen measurements by in situ sensors on remote platforms are used to determine net biological oxygen fluxes in the surface ocean. On an annual basis these fluxes are stoichiometrically related to the export of organic carbon from the upper ocean (the ocean's biological carbon pump). In situ measurements on remote platforms make it feasible to observe the annual biological oxygen flux globally, but the accuracy of these estimates during periods of high winds depends on model‐determined fluxes by bubble proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…Although we could have used an oxygen budget to estimate NCP as well, nitrate, DIC, and TA budgets were chosen for this study due to our interest in euphotic zone NCP and the sensitivity of oxygen budgets on accurate gas exchange rates at the air-sea interface, which has been addressed in a previous manuscript using the same float data set (Plant et al, 2016). Furthermore, oxygen has been used as a tracer of NCP in the Northeast Pacific in many previous studies (Bushinsky & Emerson, 2015;Emerson & Stump, 2010;Emerson et al, 2008Emerson et al, , 2019Nicholson et al, 2008;Pelland et al, 2018;etc. ); thus, we believe our oxygen budget analysis provides no further insight to the contributions cited.…”
Section: Global Biogeochemical Cyclesmentioning
confidence: 99%
“…Although we could have used an oxygen budget to estimate NCP as well, nitrate, DIC, and TA budgets were chosen for this study due to our interest in euphotic zone NCP and the sensitivity of oxygen budgets on accurate gas exchange rates at the air-sea interface, which has been addressed in a previous manuscript using the same float data set (Plant et al, 2016). Furthermore, oxygen has been used as a tracer of NCP in the Northeast Pacific in many previous studies (Bushinsky & Emerson, 2015;Emerson & Stump, 2010;Emerson et al, 2008Emerson et al, , 2019Nicholson et al, 2008;Pelland et al, 2018;etc. ); thus, we believe our oxygen budget analysis provides no further insight to the contributions cited.…”
Section: Global Biogeochemical Cyclesmentioning
confidence: 99%
“…We observed linear relationships between sensor and discrete O 2 , with offsets in the uncalibrated data typical of Aanderaa optodes whose accuracy decays over time (Bittig et al, 2018). The strong linearity between sensor and discrete data enables calibration with an average accuracy of 1%, which is required for successful field deployments (Emerson et al, 2019). Optode and GTD-derived N 2 also showed strong coherence with discrete Niskin bottle samples analyzed by mass spectrometry and could be validated to within ~1.2%.…”
Section: Field Applications and Laboratory And In Situ Testingmentioning
confidence: 69%
“…Although the solubility properties of N 2 and O 2 somewhat differ, and N 2 is subject to minor biological influences (e.g., N 2 -fixation), ΔO 2 /N 2 approximates ΔO 2 /Ar under many conditions. Oxygen and N 2 measurements have been combined to infer gas dynamics (Zhou et al, 2014;Tortell et al, 2015) and NCP from refined O 2 budgets (Emerson et al, 2019), but NCP derivation from underway ΔO 2 /N 2 remains largely underexploited. The development of a robust system for continuous O 2 /N 2 measurement thus has the potential to significantly expand oceanic NCP estimates.…”
Section: Introductionmentioning
confidence: 99%
“…High gas exchange rates and low primary production in winter sustained nearly saturated DO, even if pCO 2 % was oversaturated. Although bubble injection increasing DO% can be neglected when wind speed is lower than 10 m s −1 (Emerson et al 2019), sustained wind gusts higher than this value were observed intermittently, which could partially contribute to oversaturated DO% in surface waters. Besides, the supersaturated DO% in February was majorly controlled by high biological production.…”
Section: Discussionmentioning
confidence: 99%